2023
DOI: 10.1111/tpj.16378
|View full text |Cite
|
Sign up to set email alerts
|

A versatile CRISPR‐based system for lineage tracing in living plants

Abstract: SUMMARYIndividual cells give rise to diverse cell lineages during the development of multicellular organisms. Understanding the contribution of these lineages to mature organisms is a central question of developmental biology. Several techniques to document cell lineages have been used, from marking single cells with mutations that express a visible marker to generating molecular bar codes by CRISPR‐induced mutations and subsequent single‐cell analysis. Here, we exploit the mutagenic activity of CRISPR to allo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Plants have some advantages over animals for lineage tracing, notably that with few exceptions plant cells are immobile. Donà et al (2023) recently reported proof of concept CRISPR-based lineage tracing in Arabidopsis roots, and further showed its utility in Marchantia, concluding that plant lineage tracing can generate "a comprehensive visual map of differentiating cell files and tissue fate and help to characterize the role of key genes at developmental branch points. "…”
Section: Discussionmentioning
confidence: 99%
“…Plants have some advantages over animals for lineage tracing, notably that with few exceptions plant cells are immobile. Donà et al (2023) recently reported proof of concept CRISPR-based lineage tracing in Arabidopsis roots, and further showed its utility in Marchantia, concluding that plant lineage tracing can generate "a comprehensive visual map of differentiating cell files and tissue fate and help to characterize the role of key genes at developmental branch points. "…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, they have been applied to understanding cell fates, cell lineages, and organ development. For example, CRISPR-Cas9-based DNA-recording was used to track cellular lineages in Arabidopsis thaliana ( Arabidopsis ) and Marchantia polymorpha ( 30 ) ( Figure 3 A). Integrase-based DNA-recorders were implemented in Arabidopsis to detect the expression of transcription factors that control lateral root development, 31 and for analysis of cambium stem cells 32 ( Figure 3 B).…”
Section: Synthetic Biology Approaches For Elucidating Plant Cellular ...mentioning
confidence: 99%
“…A. A CRISPR-Cas9-based DNA-recording device 30 composed of an out-of-frame fluorescent protein (FP) with a gRNA target site at the 5′ extremity of the coding sequence. The promoter controlling Cas9 expression is activated by molecular signals (transcription factors) in progenitor cells, leading to insertion/deletion events, some of which restore the reporter reading frame, enabling the detection of daughter cells by sequencing or FP visualization.…”
Section: Synthetic Biology Approaches For Elucidating Plant Cellular ...mentioning
confidence: 99%
“…Systems based on CRISPR-Cas9 mediated mutations and subsequent DNA sequencing enabled recording of the Wnt signaling pathway in mammalian cells 15 although this approach lacked spatial resolution. DNA-based recording devices utilizing CRISPR have also been used for lineage tracing, for example in reconstructing lineages in Arabidopsis tissues 16 , zebrafish organs 17 , and in development of a lineage tracing mouse line 18 . Researchers have also utilized the DNA recombination abilities of integrases for similar DNA-based recording approaches.…”
Section: Introductionmentioning
confidence: 99%